Analisis Stabilitas Lereng Ruas Jalan Sicincin–Malalak Km 31 Kecamatan Malalak, Kabupaten Agam, Provinsi Sumatera Barat - Evansharsal Suedi; Raimon Kopa; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2018)
Landslide natural disasters are one of the natural disasters that cause fatalities and property. Based on the frequency of events, intensity, and geological conditions, the area of Kabupaten Agam Sumatera is an area that must be aware of the potential for landslidesthis is shown in the vulnerability map of soil movement by the Dinas Energi dan Sumberdaya Kabupaten Agam Sumatra Barat. Malalak District Agam Regency is one of the zones that has a high vulnerability to soil movement. This is shown in the Agam Regency Landslide Hazard Map which needs to consider slope security because it has many factors triggering landslides, especially in its purpose as road access.This research is classified into applied research. Slope stability in this study will use slope geometry data, physical properties, mechanical properties, Rock Quality Designation (RQD) rock mass classification, Rock mass Rating (RMR) and using the Bishop Simplified method (FK or Safety Factor) supported by software. analysis of avalanche types and security factor analysis.As a result of the research carried out on the Malalak KM 31 road section, it can be concluded the following points. The rock type of the slope compiler is andesite with the value of rock mass classification with a value of RMR of 68 including in the second (II) class rocks with good rock categories. The results of kinematic analysis indicate the potential for Baji avalanches. Ground vibration that is received by the slope affects the stability value with the value of the earthquake vibration based on the Indonesian seismic map of 0.6 g. In determining the value of the actual slope safety factor using security factor analysis software obtained FK value in dry conditions of 4,000, natural conditions of 3,979, saturation conditions of 3,966 this shows the condition of the water in the rock does not significantly affect the value of slope safety factor. Whereas the value of the safety factor with the influence of vibration is obtained in a dry condition is 2,659, the natural condition is 2,642, the saturation condition is 2,638 from the result of the vibration effect on the stability of the slope has a considerable decrease in the safety value of the slope but shows that the slope condition is still stable. Keywords: Slope Stability,Road ,Ground Vibration ,RMR, Safety Factor